2008
DOI: 10.1007/s10530-008-9376-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-native plant invasions of United States National Parks

Abstract: The United States National Park Service was created to protect and make accessible to the public the nation's most precious natural resources and cultural features for present and future generations. However, this heritage is threatened by the invasion of non-native plants, animals, and pathogens. To evaluate the scope of invasions, the USNPS has inventoried non-native plant species in the 216 parks that have significant natural resources, documenting the identity of non-native species. We investigated relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 71 publications
3
59
0
3
Order By: Relevance
“…They further indicate the need for careful planning of tourist access ways when developing management plans for national parks. Allen et al [42] identified a close correlation between the number of visitors and the alien weed population. It is planned that this preliminary study will lead to in depth investigation into the correlation of non-native plant species with other aspects, such as native, rare, threatened and endangered plant species; park area; elevation; roads, trials, and rivers distances; temperature; longitude; latitude; and other attributes along the lines with discussed by Allen et al [42].…”
Section: Discussionmentioning
confidence: 97%
“…They further indicate the need for careful planning of tourist access ways when developing management plans for national parks. Allen et al [42] identified a close correlation between the number of visitors and the alien weed population. It is planned that this preliminary study will lead to in depth investigation into the correlation of non-native plant species with other aspects, such as native, rare, threatened and endangered plant species; park area; elevation; roads, trials, and rivers distances; temperature; longitude; latitude; and other attributes along the lines with discussed by Allen et al [42].…”
Section: Discussionmentioning
confidence: 97%
“…However, the experimental materials are inconsistent [25,26]. The number of non-native species depends on the number of indigenous species, where a larger variety of local flora exhibits a greater effect on the number of non-native plants.…”
Section: Phacelia Tanacetifolia Benthammentioning
confidence: 99%
“…Nature reserves world-wide contain increasing numbers of non-native plant species in their flora (e.g., Allen et al 2009, Barnett et al 2007, Pyšek et al 2003. Invasion by non-native plants occurred both before and after establishment of nature reserves.…”
Section: Introductionmentioning
confidence: 99%